PERANAN KUALITAS KEHIDUPAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN MOTIVASI KERJA: STUDI PADA USAHA KECIL MENENGAH - Bismala, Lila (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Human resources have an important role as a component of company competitiveness, so it needs serious attention. Along with the increasing role of small and medium enterprises in the country's economy, attention to SME employees also needs attention. This has led to a study of organizational behavior within the SME scope. This study aims to analyze the role of the quality of work life and organizational culture on work motivation with job satisfaction as an intervening variable. The sample in this study were employees who worked at SMEs, a number of 100 people. By using path analysis, the results show that there is an influence of organizational culture and the quality of work life on job satisfaction simultaneously. And there is the influence of organizational culture, quality of work life and job satisfaction simultaneously. However, in this study, the results of data processing indicate that job satisfaction does not function as an intervening variable for organizational culture and the quality of work life on work motivation.